2010
DOI: 10.1111/j.1529-8019.2010.01307.x
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and the metabolic syndrome

Abstract: Psoriasis is an inflammatory, immune-mediated cutaneous disorder that has recently been recognized as systemic disease that is associated with multiple comorbidities such as depression, obesity, and the metabolic syndrome. The metabolic syndrome is the constellation of abdominal obesity, dyslipidemia, hypertension and insulin resistance, and presence of the metabolic syndrome significantly increases a patient's risk for cardiovascular disease, stroke and type 2 diabetes. Recent studies have found that psoriasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 60 publications
1
47
0
8
Order By: Relevance
“…Researchers have focused their attention on comorbidities in psoriasis including: type 2 diabetes, atherosclerosis, hypertension, myocardial infarction, depression and obesity. Hyperuricemia in patients with psoriasis has been noted [1,3,[41][42][43][44][45]. It seems that metabolic syndrome, for which the coexistence of well-known cardiovascular disease risk factors is characteristic, may be the connection between cardiovascular complications and type 2 diabetes in patients with psoriasis [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have focused their attention on comorbidities in psoriasis including: type 2 diabetes, atherosclerosis, hypertension, myocardial infarction, depression and obesity. Hyperuricemia in patients with psoriasis has been noted [1,3,[41][42][43][44][45]. It seems that metabolic syndrome, for which the coexistence of well-known cardiovascular disease risk factors is characteristic, may be the connection between cardiovascular complications and type 2 diabetes in patients with psoriasis [1].…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is an immune mediated inflammatory skin disease characterized by epidermal hyperproliferation, impaired differentiation of keratinocytes, excessive angiogenesis and immunological dysfunction [1][2][3]. The immunologic cells engaged in the pathogenesis of psoriasis which have been the focus of attention in recent years include not only lymphocytes Th1, but also Th17, Th22 and regulatory T lymphocytes (Treg).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La importancia del SM radica en el incremento del riesgo de sufrir otras comorbilidades, fundamentalmente enfermedad arterial coronaria, infarto de miocardio, ictus y diabetes mellitus de tipo 2 3 . El SM se caracteriza por un incremento de la actividad de las células TH1, lo que sugiere que, en determinadas enfermedades inflamatorias, como la psoriasis, estarían unidas por la misma desregulación de las vías de la inflamación 4 .…”
Section: Síndrome Metabólicounclassified
“…Recent studies have found that psoriasis patients are at increased risk for metabolic syndrome as well as the individual components of metabolic syndrome, and the two diseases appear linked through a common mechanism of inflammation. Psoriasis treatments have been shown to reduce the risk of developing metabolic syndrome components and comorbidities (Alsufyani et al, 2010). The prevalence of obesity in psoriatic patients within the "Utah Psoriasis Initiative" (UPI) population was higher than that in the general Utah population.…”
Section: Metabolic Syndromementioning
confidence: 99%